Analysis of nursing problems in patients undergoing extracorporeal membrane oxygenation - Vičkačkaitė, Eglė; Mikaliūkštienė, Aldona; Surgunt, Natalja (Slauga. Mokslas ir praktika, 2023)
Extracorporeal membrane oxygenation (ECMO) is an artificial circulatory technique that maintains vital lung and/or heart function during critical conditions. ECMO is considered a complex clinical activity requiring critical decisions and rapid medical response, especially in emergency situations. Anaesthesia and critical care nurses face many challenges in their work, and patients with critical medical conditions are particularly stressful. The nursing process becomes even more complex when the patient is on ECMO. The aim of this study was to analyse from a theoretical perspective the nursing characteristics and problems in the care of patients undergoing extracorporeal membrane oxygenation.The research method was a review of scientific articles using the following key words: anaesthesia and intensive care nurses, nurses knowledge, nursing problems, extracorporeal membrane oxygenation, and combinations of these with the words "and" "or". PubMed, Cochrane ClinicalKey, BMJ Best Practice, Science Direct and Google Scholar databases were searched for research articles. The literature review included open access and full-length articles published between 2016 and 2022 and written in English.The results showed that anaesthesia and intensive care nurses need to demonstrate in-depth knowledge and skills, to be able to react quickly to meet individual patient care needs, to recognise early complications of ECMO, to ensure the patient's recovery and to improve quality of life.
Keywords: anaesthesia and intensive care nurses; nurses' knowledge; nursing problems; extracorporeal membrane oxygenation; ECMO